Inhibitory effect of cinnamomum burmanii extract against Staphylococcus aureus on acrylic resin denture bases - Eka SI. Sari; Carolina Marpaung; Thomas Alberto (Indonesia Prosthodontic Association, 2025)
Background: Denture base acrylic resin properties is susceptible to bacteria colonization which further induce post insertion problems. Objectives: This study aimed to evaluate the antibacterial effect of Cinnamomum burmanii extract against Staphylococcus aureus on heat-cured acrylic resin denture base material. Materials and method: An in vitro post-test only control group design was used with 28 acrylic resin plates (9x9x3 mm) contaminated with S. aureus (0.5 McFarland). Samples were randomly divided into seven groups (n=4): positive control (0.2% chlorhexidine), negative control (aquades), and five treatment groups immersed in C. burmanii extract at concentrations of 25%, 12.5%, 6.25%, 3.125%, and 1.56%. Immersion was performed for 8 hours, after which bacterial colony counts were determined using the Total Plate Count method. Results: Phytochemical screening of the extract showed the presence of flavonoids, alkaloids, tannins, and triterpenoids. All concentrations of C. burmanii extract reduced S. aureus colonies compared to the negative control, with a significant overall difference among groups. The 25% concentration demonstrated the lowest mean colony count and showed an antibacterial effect approaching that of 02% chlorhexidine. Conclusion: These findings suggest that C. burmanii extract, particularly at 25% concentration, has potential as a natural denture cleanser alternatives for reducing S. aureus colonization on acrylic resin bases.